GREEN INVOLVEMENT, WORKPLACE WELL-BEING, AND CAREER PLANNING AFFECT TURNOVER INTENTION; IS IT POSSIBLE? - Abyan Arfari; Dita Oki Berlyanti; Wiwik Robiatul Adawiyah (Jurnal Konseling Pendidikan Islam, 2023)
The research method used in this research is quantitative descriptive, involving 1 dependent variable and 3 independent variables; the independent variables are Green Involvement, Workplace Well Being, and Career Planning, while the dependent variable is Turnover Intention. The results of the data analysis show that green involvement has a positive influence on turnover intentions. This can be seen based on a significance value of.007 0.05, which indicates that H 0 is rejected, H a is supported with a value () of.278. Workplace well-being has a positive influence on turnover intention. This can be seen based on a significance value of.194 0.05, which indicates that H0 is rejected, Ha is supported with a value () of.091, and career planning has a positive influence on turnover intention. This is evident from the significance value of.000 0.05, indicating that H 0 is rejected and H a is supported by a value () of.710. The conclusion of this research is that employees agree with the implementation of green engagement, wellbeing at work, and career planning to reduce high levels of transfer intentions.